Spatial and risk factor analyses of vector-borne pathogens among shelter dogs in the Eastern United States. - Hazelrig, Corinna M; Gettings, Jenna R; Cleveland, Christopher A; Varela-Stokes, Andrea.; Majewska, Ania A; Hubbard, Kris.; Burton, K. Wade.; Yabsley, Michael J (Tufts University. Tisch Library., 2023)
Keywords: Co-infections, Heartworm, Tick-borne disease, Vector-borne disease.; Springer Open.